2021
DOI: 10.2147/jir.s322391
|View full text |Cite
|
Sign up to set email alerts
|

Serum C1q Levels Have Prognostic Value for Sepsis and are Related to the Severity of Sepsis and Organ Damage

Abstract: Objective To explore the clinical application value of serum complement component C1q levels in sepsis. Methods The clinical data and laboratory examination data of 320 research subjects (including 132 cases as sepsis group, 93 cases as nonsepsis group and 95 cases as control group) who were diagnosed and treated in Renmin Hospital of Wuhan University from July 2020 to March 2021 were collected. We compared the levels of each index among the three groups and further ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In our study, a strong association between C1QC and organ dysfunction is evidenced. In a recent study, Li et al [60] found that C1QC levels were significantly reduced in the serum of sepsis patients. This decrease was associated with a high AUC not only with higher mortality, but also with a higher SOFA score with an AUC for sepsis prognosis, higher SOFA and mortality.…”
Section: Complementmentioning
confidence: 96%
“…In our study, a strong association between C1QC and organ dysfunction is evidenced. In a recent study, Li et al [60] found that C1QC levels were significantly reduced in the serum of sepsis patients. This decrease was associated with a high AUC not only with higher mortality, but also with a higher SOFA score with an AUC for sepsis prognosis, higher SOFA and mortality.…”
Section: Complementmentioning
confidence: 96%
“… 10 Moreover, research has shown that C1q serves as a valuable marker for assessing the severity of sepsis and organ damage. 11 …”
Section: Introductionmentioning
confidence: 99%